WC-Ni-Cr hard alloy and preparation method and application thereof
By adding a polycarboxyl complexing agent to the raw materials of WC-Ni-Cr cemented carbide and coordinating complexing with Ni powder, the problem of uneven composition caused by Ni powder agglomeration is solved, and the mechanical properties and cost-effectiveness of the alloy are improved.
Patent Information
- Application Number
- CN202411945319.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-25
AI Technical Summary
During the preparation process of WC-Ni-Cr cemented carbide, due to the mutual agglomeration of Ni powder, forming a cold welding effect, resulting in uneven composition and Ni pools appear, affecting the mechanical properties of the alloy.
Add a polycarboxyl complexing agent to the raw material to coordinate and complex with Ni powder to build a protective layer to avoid agglomeration of Ni powder and ensure uniform composition.
Through the use of complexing agent, the formation of Ni pools is reduced, the uniformity of the bonded phase and the mechanical properties of the cemented carbide are improved, and the raw material cost and process cost are reduced.
Smart Images

Figure CN119876725A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of cemented carbide, and in particular relates to a WC-Ni-Cr cemented carbide and a preparation method and application thereof. Background Art
[0002] Cemented carbide is an alloy material made by powder metallurgy from refractory carbides and binder metals (such as Co, Fe, and Ni). This material combines the toughness of the binder phase with the hardness of the carbide particles, resulting in high hardness and wear resistance, good thermal and chemical stability, excellent oxidation and corrosion resistance, high elastic modulus, and compressive strength. Cemented carbide is widely used in mining drilling tools, machining tools, wear-resistant parts, and mold manufacturing, and is known as the "teeth of industry" for its excellent properties.
[0003] WC-Ni cemented carbide is lower in hardness and strength than WC-Co alloy, but has higher corrosion resistance and oxidation resistance. In corrosive environments, WC-Ni alloy shows obvious advantages. The complete substitution of Ni for Co can greatly improve the corrosion resistance of the alloy. At the same time, the addition of Cr can improve the mechanical properties of WC-Ni cemented carbide. However, during the preparation process of WC-Ni-Cr cemented carbide, due to the good plasticity of Ni, during the wet grinding process of cemented carbide, as the wet grinding time increases, the Ni powder is continuously broken and deformed to a certain extent, the surface activity increases, the powder agglomeration increases, and cold welding occurs, resulting in uneven distribution of the various components in the mixture. If the binder phase powder cannot be effectively dispersed, it is easy to cause agglomeration. After the mixture is formed and sintered, Ni pools are likely to appear in the alloy structure. This defective organizational structure will lead to a significant decrease in the mechanical properties of the cemented carbide.
[0004] In order to overcome the problem of Ni pool generated by aggregation of the binder phase during the preparation process of WC-Ni-Cr alloy, Chinese patent CN105695837B discloses a method for preparing WC-Ni fine-grained cemented carbide, which overcomes the defect caused by the long grinding time of the binder component caused by grinding the binder component Ni and the hard phase WC together in the previous cemented carbide production. Fine-grained Ni powder with a Fisher particle size of 0.5-1.0μm and a segmented grinding process are used to reduce the wet grinding time of the binder phase, thereby reducing or avoiding the formation of Ni pool in the sintering process. The method uses finer-grained Ni powder, which greatly increases the raw material cost; at the same time, the surface energy of fine-grained Ni powder in the wet grinding process is actually greater than that of coarse-grained Ni powder, and particles are more likely to agglomerate during the wet grinding process, resulting in serious grinding time and poor reproducibility between batches. Therefore, in the absence of a surface protective agent, the use of fine-grained Ni powder is a temporary solution that does not address the root cause. At the same time, since the wet grinding time of Ni powder is short (14h-18h), the mixing uniformity with other carbides is poor for ultrafine cemented carbide, which easily leads to uneven composition of the final cemented carbide.
[0005] Chinese patent CN110102769B discloses a wet grinding method that is beneficial to the uniformity of the microstructure of high-bonding phase cemented carbide. During the wet grinding process, a surface dispersant is added, and its mass is 0.05%-1.7% of the mass of the mixture. The surface dispersant is composed of PEG1000, dodecyl glycoside, and ethylene glycol monostearate, and its mass is 0.03%-1.5%, 0.01%-0.1%, and 0.01%-0.1% of the mass of the mixture, respectively. Due to the amphiphilic nature of the surface dispersant chain segment (one end is hydrophilic and the other end is lipophilic), a hydrophobic force forms a protective layer on the surface of the Co powder to prevent the formation of a pool of the bonding phase Co. Although this method can effectively form a protective layer on the bonding phase surface, because the hydrophobic force is a relatively weak intermolecular interaction force, the force intensity is low, and the protective layer easily falls off under external energy driving, thereby losing its protective effect on the bonding phase metal. A large amount of heat energy is generated during the wet grinding process, which has a significant destructive effect on the protective layer on the bonding phase surface.
[0006] Chinese patent CN112391548B discloses a method for preparing WC-Ni fine-grained cemented carbide. Nickel chloride, cerium chloride, and the like are added to sodium borohydride under the protection of polyethylene glycol for reduction. While this method ensures small metal particle size, the use of metal chlorides and sodium borohydride for redox reactions significantly increases raw material costs. Furthermore, residual elements such as Na, B, and Cl are difficult to remove during subsequent pressing and sintering processes, ultimately resulting in defects in the finished product and affecting the strength of the cemented carbide. Summary of the Invention
[0007] Based on the above, the main purpose of the present invention is to provide a WC-Ni-Cr cemented carbide and a preparation method thereof. The WC-Ni-Cr cemented carbide improves the uniformity of the WC-Ni-Cr cemented carbide binder phase by adding a complexing agent to the raw nickel powder to form a complex with Ni.
[0008] To this end, in the first aspect, the present invention proposes a WC-Ni-Cr cemented carbide, whose raw materials include: Ni powder, Cr2C3 powder, a complexing agent and WC powder. In terms of mass, in the cemented carbide, the contents of Ni powder and Cr2C3 powder are 6-15 mass parts and 1-5 mass parts, respectively, the content of the complexing agent is 15%-30% of the mass of the Ni powder, and the content of the WC powder is 60-95 mass parts; wherein the complexing agent is a polycarboxyl complexing agent.
[0009] In existing WC-Ni-Cr cemented carbide, cold welding occurs due to the mutual agglomeration of Ni powder, resulting in uneven distribution of the components in the raw material (also referred to as a mixture), which in turn causes the formation of Ni pools in the cemented carbide structure, thereby affecting the mechanical properties of the cemented carbide. The present invention adds a complexing agent to the raw material, and the complexing agent interacts with the Ni powder to avoid the mutual agglomeration of Ni powder, thereby ultimately avoiding the formation of Ni pools in the cemented carbide structure. In addition, since the interaction between the complexing agent and the metal is saturated, the interaction between the complexing agent and the metal is better when the complexing agent is within the above-mentioned ratio range. If the amount of complexing agent is too small, the efficiency of complexing with Ni powder decreases, affecting the uniformity of the bonding phase and the strength of the final product and other mechanical properties; if the amount of complexing agent is too large, the excessive amount of complexing agent leads to increased costs, and the time for sintering to remove the complexing agent increases, resulting in increased final process costs.
[0010] As a specific embodiment of the present invention, the polycarboxyl complexing agent coordinates with metal Ni. In the present invention, the polycarboxyl complexing agent protects the central metal by coordinating with metal Ni, thereby greatly reducing the shedding of the protective layer during wet grinding and preventing the mutual agglomeration of Ni powder.
[0011] As a specific embodiment of the present invention, the polycarboxyl complexing agent contains more than 3 carboxyl groups, preferably, the polycarboxyl complexing agent contains 3 to 6 carboxyl groups. The present invention unexpectedly discovered that when the coordination number in the complexing agent molecule is greater than or equal to 3, it can have a better complexing effect with Ni.
[0012] As a specific embodiment of the present invention, the molecular weight of the polycarboxyl complexing agent is 150-300 g / mol. The present invention unexpectedly found that small molecule complexing agents with a molecular weight of 150-300 g / mol have a higher ratio of complexed atoms than macromolecular complexing agents, thereby improving complexing efficiency and reducing process costs.
[0013] As a specific embodiment of the present invention, the polycarboxyl complexing agent is selected from at least one of citric acid (CA), ethylenediaminetetraacetic acid (EDTA), and methylglycine diacetic acid (MGDA). The elemental composition of the polycarboxyl complexing agent selected in the present invention only contains four elements: C, H, O, and N. The residual C element can be solved by adjusting the carbon content in the process. The latter three elements are easily removed from the blank before sintering, so that they do not remain in the cemented carbide, thereby ensuring the structure and performance of the sintered product.
[0014] In a specific embodiment of the present invention, the polycarboxyl complexing agent is citric acid, and its addition amount is 15%-20% of the mass of the Ni powder. When the citric acid addition amount is within the above range, the Ni powder complexing efficiency is further increased, thereby improving the uniformity of the binder phase and the mechanical properties such as the strength of the final product.
[0015] In a specific embodiment of the present invention, the polycarboxyl complexing agent is EDTA, and its addition amount is 25%-30% of the mass of the Ni powder. When the EDTA addition amount is within the above range, the Ni powder complexing efficiency is further increased, thereby improving the uniformity of the binder phase and the mechanical properties such as strength of the final product.
[0016] In a specific embodiment of the present invention, the polycarboxyl complexing agent is methylglycine diacetic acid, and its addition amount is 20%-25% of the mass of the Ni powder. When the amount of methylglycine diacetic acid added is within the above range, the Ni powder complexing efficiency is further increased, thereby improving the uniformity of the binder phase and the mechanical properties such as strength of the final product.
[0017] As a specific embodiment of the present invention, the Ni powder has a Fisher particle size of 0.5-5.0 μm.
[0018] As a specific embodiment of the present invention, the Cr2C3 powder has a Fisher particle size of 0.5-3.0 μm.
[0019] As a specific embodiment of the present invention, the WC powder has a Fisher particle size of 0.1-2.0 μm.
[0020] As a specific embodiment of the present invention, in the cemented carbide, the content of the WC powder is 80-9 parts by mass.
[0021] To this end, in a second aspect, the present invention provides a method for preparing the above-mentioned WC-Ni-Cr cemented carbide, comprising batching, wet grinding, drying, pressing and sintering.
[0022] As a specific embodiment of the present invention, the wet grinding conditions include: a ball-to-material ratio of 3.0-12.0:1, a liquid-to-solid ratio of 100-800 mL / kg, and a wet grinding time of 48-120 h.
[0023] As a specific embodiment of the present invention, the drying conditions include: spray drying temperature of 70-150° C., and drying time of 0.5-6.0 h.
[0024] As a specific embodiment of the present invention, the sintering conditions include: sintering temperature 1300-1600° C., sintering pressure 0-10 MPa, and sintering time 2-6 hours.
[0025] As a specific embodiment of the present invention, the wet grinding includes the following steps: pre-wet grinding the first part of the raw materials with the forming agent and the wet grinding medium; then adding the second part of the raw materials and continuing to wet grind again; the first part of the raw materials and the second part of the raw materials are all the raw materials; the time of the pre-wet grinding and re-wet grinding is the wet grinding time.
[0026] As a specific embodiment of the present invention, the first part of the raw material can be the remaining raw materials except Ni powder, and all the Ni powder is used as the second part of the raw material; or the raw material containing a part of Ni powder can be used as the first part of the raw material, and the remaining Ni powder is used as the second part of the raw material. The mass of the Ni powder in the second part of the raw material is usually greater than or equal to the Ni powder of the aforementioned part.
[0027] As a specific embodiment of the present invention, the molding agent is paraffin or PEG.
[0028] As a specific embodiment of the present invention, the wet grinding medium is xylene, alcohol or hexane, preferably alcohol or hexane.
[0029] As a specific embodiment of the present invention, the volume concentration of the alcohol is 90% to 100%.
[0030] As a specific embodiment of the present invention, the ratio of the wet grinding medium to the raw material is 200 ml / kg to 400 ml / kg, preferably 250 ml / kg to 350 ml / kg.
[0031] To this end, in a third aspect, the present invention proposes an application of the above-mentioned WC-Ni-Cr cemented carbide or the WC-Ni-Cr cemented carbide prepared by the above-mentioned preparation method in wear-resistant parts, cutting tools and drilling tools.
[0032] The beneficial effects of the present invention are as follows:
[0033] (1) In the present invention, a polycarboxyl complexing agent is added to the raw material (or mixed material). Through the interaction between the polycarboxyl complexing agent and the Ni powder, a protective layer is constructed outside the bonding phase metal, which reduces the aggregation of Ni powder and the formation of Ni pools, increases the strength of the force between the protective layer and the surface of the Ni powder, and reduces and prevents the protective layer from falling off the surface of the Ni powder during the wet grinding process.
[0034] (2) The complexing agent in the present invention is a small molecular weight polycarboxyl complexing agent, which further increases the carboxyl concentration in the molecule, improves the complexing efficiency, and reduces the raw material cost.
[0035] (3) The complexing agent in the present invention preferably contains only four elements: C, H, O, and N, so as not to produce defects in the cemented carbide after sintering, thereby ensuring the structure and strength of the cemented carbide product after sintering.
[0036] (5) The complexing agent in the present invention preferably has a specific ratio with Ni powder, which ensures sufficient Ni powder complexing efficiency and product performance while reducing raw material costs and removal process costs;
[0037] (6) The preparation process of the cemented carbide of the present invention is simple, requiring only the addition of a complexing agent during the wet grinding process, which does not affect the subsequent process technology route and does not require additional steps. During the sintering process, the polycarboxyl complexing agent can be completely removed during the removal of the forming agent, without changing the sintering process curve. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 Schematic diagram of the complexation between the polycarboxyl complexing agent and Ni powder in the raw materials of the WC-Ni-Cr hard alloy of the present invention;
[0039] Figure 2 The microstructure of the WC-Ni-Cr cemented carbide provided in Comparative Example 1;
[0040] Figure 3 The microstructure diagram of the WC-Ni-Cr cemented carbide provided in Example 1;
[0041] Figure 4 The microstructure diagram of the WC-Ni-Cr cemented carbide provided in Example 2;
[0042] Figure 5 This is the microstructure diagram of the WC-Ni-Cr cemented carbide provided in Example 3. DETAILED DESCRIPTION
[0043] The technical solution of the present invention is further illustrated by specific embodiments. It should be understood by those skilled in the art that the embodiments are merely for the purpose of helping to understand the present invention and should not be construed as specific limitations of the present invention. Where specific conditions are not specified in the examples, the methods are carried out according to conventional conditions or the conditions recommended by the manufacturer. Where the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.
[0044] (1) Raw materials
[0045] Paraffin wax, brand 56.
[0046] Citric acid CA, chemical formula C6H8O7, CAS number: 77-92-9.
[0047] Ethylenediaminetetraacetic acid EDTA, chemical formula C 10 H 16 N2O8, CAS number: 60-00-4.
[0048] Methylglycine diacetate MGDA, chemical formula C7H 11 NO6, CAS number: 29578-05-0.
[0049] Example 1
[0050] Combine Figure 1 As shown, the method for preparing WC-Ni-Cr cemented carbide in this embodiment is:
[0051] (1) Ingredients: 2.7 parts by mass of Cr2C3 powder with a Fisher particle size of 1.0 μm, 1.35 parts by mass of citric acid, and 84.95 parts by mass of WC powder with a Fisher particle size of 0.6 μm are taken as the first part of raw materials, and 9.0 parts by mass of Ni powder with a Fisher particle size of 2.0 μm is taken as the second part of raw materials. The first part of raw materials and the second part of raw materials are the total raw materials.
[0052] (2) Wet grinding in a ball mill: add 2.0 parts by mass of liquid paraffin to the first part of the raw materials, and add 300 mL / kg (total raw materials + liquid paraffin) of industrial alcohol (volume concentration 100%), with a ball-to-material ratio of 6:1. After mixing, pre-wet grind for 25 hours, then add the second part of the raw materials and continue wet grinding for 75 hours to obtain the final mixture;
[0053] (3) The mixture was spray-dried at an outlet temperature of 90° C. for 2 h, pressed into shape, and then sintered at a high temperature of 1450° C. and 7.5 MPa for 4 h to obtain a WC-Ni-Cr cemented carbide.
[0054] Example 2
[0055] The difference from Example 1 is that 1.35 parts by mass of citric acid is replaced by 1.6 parts by mass of citric acid, and the amount of WC powder is 84.70 parts by mass.
[0056] Example 3
[0057] The difference from Example 1 is that 1.35 parts by mass of citric acid is replaced by 1.8 parts by mass of citric acid, and the amount of WC powder is 84.50 parts by mass.
[0058] Example 4
[0059] The difference from Example 1 is that 1.35 parts by mass of citric acid is replaced by 2.26 parts by mass of ethylenediaminetetraacetic acid, and the amount of WC powder is 84.05 parts by mass.
[0060] Example 5
[0061] The difference from Example 4 is that 2.26 parts by mass of ethylenediaminetetraacetic acid is replaced by 2.5 parts by mass of ethylenediaminetetraacetic acid, and the amount of WC powder is 83.80 parts by mass.
[0062] Example 6
[0063] The difference from Example 4 is that 2.26 parts by mass of ethylenediaminetetraacetic acid is replaced by 2.7 parts by mass of ethylenediaminetetraacetic acid, and the amount of WC powder is 83.60 parts by mass.
[0064] Example 7
[0065] The difference from Example 1 is that 1.35 parts by mass of citric acid is replaced by 1.8 parts by mass of methylglycine diacetic acid, and the amount of WC powder is 84.50 parts by mass.
[0066] Example 8
[0067] The difference from Example 7 is that 1.8 parts by mass of methylglycine diacetic acid is replaced by 2.0 parts by mass of methylglycine diacetic acid, and the amount of WC powder is 84.30 parts by mass.
[0068] Example 9
[0069] The difference from Example 7 is that 1.8 parts by mass of methylglycine diacetic acid is replaced by 2.25 parts by mass of methylglycine diacetic acid, and the amount of WC powder is 84.05 parts by mass.
[0070] Comparative Example 1
[0071] Preparation of WC-Ni-Cr cemented carbide, the specific preparation method is:
[0072] (1) Ingredients: 2.7 parts by mass of Cr2C3 powder with a Fisher particle size of 1.0 μm and 84.95 parts by mass of WC powder with a Fisher particle size of 0.6 μm are taken as the first part of raw materials, and 9.0 parts by mass of Ni powder with a Fisher particle size of 2.0 μm are taken as the second part of raw materials. The first part of raw materials and the second part of raw materials are the total raw materials.
[0073] (2) Wet grinding in a ball mill: add 2.0 parts by mass of liquid paraffin to the first part of the raw materials, and add 300 mL / kg (total raw materials + liquid paraffin) of industrial alcohol (volume concentration 100%), with a ball-to-material ratio of 6:1. After mixing, pre-wet grind for 25 hours, then add the second part of the raw materials and continue wet grinding for 75 hours to obtain the final mixture;
[0074] (3) The mixture was spray-dried at an outlet temperature of 90° C. for 2 h, pressed into shape, and then sintered at a high temperature of 1450° C. and 7.5 MPa for 4 h to obtain a WC-Ni-Cr cemented carbide.
[0075] Table 1: Weight of each raw material in Examples 1-9
[0076]
[0077] Test Example 1
[0078] The cemented carbides prepared in Comparative Example 1 and Examples 1-3 were examined under a metallographic microscope to obtain microstructure diagrams. The microstructure diagrams were analyzed using the image processing software ImageJ to obtain grayscale value data of the metallographic images of each sample, which are summarized in Table 2.
[0079] Table 2 Image grayscale value analysis results of Comparative Example 1 and Examples 1-3
[0080] Sample number Maximum grayscale value Average gray value Standard deviation Regional area share / % Comparative Example 1 221 44.498 41.536 97.102 Example 1 214 39.622 33.494 97.938 Example 2 167 33.966 22.480 98.354 Example 3 215 35.470 30.358 96.764
[0081] In Comparative Example 1 and Examples 1-3, the total proportion of Ni powder is 9.0%, and the performance of the final cemented carbide is regulated only by adjusting the feed ratio of the complexing agent. In Table 2, the grayscale represents the voids or defects of the cemented carbide material. The larger the average grayscale value, the more voids the material has, which is directly caused by the uneven dispersion of Ni. From the analysis data in Table 2, it can be seen that the average grayscale value of the image obtained in Example 2 is the smallest, indicating that the Ni powder in the material is well dispersed, thereby compensating for the defects. At the same time, in the regional proportion data of the grayscale, it is found that the grayscale distribution of Example 2 has the largest proportion, which also shows that the Ni distribution is more uniform in the entire area. With the increase of the complexing agent feed, the dispersion of the Ni powder gradually improves, but excessive complexing agent will also lead to an increase in the average grayscale value and a decrease in the grayscale proportion. It is speculated that the excessive complexing agent is more difficult to remove in the dewaxing stage before the sintering process, causing a local increase in the carbon-tungsten ratio inside the product, resulting in defects.
[0082] In Example 4-9, only the polycarboxyl complexing agent was replaced, and the remaining operations and analyses were consistent with those in Example 1-3. Therefore, the application effects were similar to those in Example 1-3 and will not be described in detail.
[0083] The above description of the embodiments is intended to facilitate understanding and application of the present invention by those skilled in the art. It will be apparent that those skilled in the art can readily make various modifications to these embodiments and apply the general principles described herein to other embodiments without requiring inventive effort. Therefore, the present invention is not limited to the embodiments described herein. Improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A WC-Ni-Cr cemented carbide, characterized in that: The raw materials include: Ni powder, Cr2C3 powder, complexing agent and WC powder; in terms of weight, in the hard alloy, the content of Ni powder and Cr2C3 powder is 6-15 weight parts and 1-5 weight parts respectively, the content of the complexing agent is 15%-30% of the weight of the Ni powder, and the content of the WC powder is 60-95 weight parts; wherein the complexing agent is a polycarboxyl complexing agent.
2. The cemented carbide according to claim 1, characterized in that: The polycarboxyl complexing agent is coordinated with the metal Ni in the Ni powder; and / or the polycarboxyl complexing agent contains more than 3 carboxyl groups; and / or the molecular weight of the polycarboxyl complexing agent is 150-300 g / mol.
3. The cemented carbide according to claim 2, characterized in that: The polycarboxyl complexing agent is selected from at least one of citric acid, ethylenediaminetetraacetic acid, and methylglycine diacetic acid.
4. The cemented carbide according to claim 3, characterized in that: The polycarboxyl complexing agent is citric acid, and the added amount thereof is 15%-20% of the mass of the Ni powder.
5. The cemented carbide according to claim 3, characterized in that: The polycarboxyl complexing agent is ethylenediaminetetraacetic acid, and the added amount thereof is 25%-30% of the mass of the Ni powder.
6. The cemented carbide according to claim 3, characterized in that: The polycarboxyl complexing agent is methylglycine diacetic acid, and the added amount thereof is 20%-25% of the mass of the Ni powder.
7. The cemented carbide according to any one of claims 1 to 6, characterized in that: The Ni powder has a Fisher particle size of 0.5-5.0 μm; and / or, The Cr2C3 powder has a Fisher particle size of 0.5-3.0 μm; and / or, The WC powder has a Fisher particle size of 0.1-2.0 μm; and / or, In the cemented carbide, the content of the WC powder is 80-9 parts by mass.
8. A method for preparing the WC-Ni-Cr hard alloy according to any one of claims 1 to 7, characterized in that: It includes batching, wet grinding, drying, pressing and sintering.
9. The preparation method according to claim 8, characterized in that: The wet grinding conditions include: ball-to-material ratio of 3.0-12.0:1, liquid-to-solid ratio of 100-800 mL / kg, wet grinding time of 48-120 h; and / or The drying conditions include: spray drying temperature 70-150°C, drying time 0.5-6.0h; and / or The sintering conditions include: sintering temperature of 1300-1600° C., sintering pressure of 0-10 MPa, and sintering time of 2-6 hours.
10. Use of the WC-Co cemented carbide according to any one of claims 1 to 7 or the WC-Co cemented carbide prepared by the preparation method according to claim 8 or 9 in wear-resistant parts, cutting tools and drilling tools.
Citation Information
Patent Citations
A kind of preparation method of wc-ni fine-grained cemented carbide
CN105695837B
A wet grinding method that improves the uniformity of microstructure in cemented carbide with high binder phase
CN110102769B
A method for preparing WC-Ni fine-grained cemented carbide
CN112391548B